Will more Kelantan PAS elected representatives jump ship? - New Sabah Times English, (KK) (New Sabah Times English (KK), 2015)
KOTA BAHARU: The political atmosphere in Kelantan heated up a little following rumors that 10 PAS elected representatives in the state would jump ship and join Parti Amanah Rakyat (Amanah) in January next year.